If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -29 = -77 + 2x Reorder the terms: -29 + 8x = -77 + 2x Solving -29 + 8x = -77 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -29 + 8x + -2x = -77 + 2x + -2x Combine like terms: 8x + -2x = 6x -29 + 6x = -77 + 2x + -2x Combine like terms: 2x + -2x = 0 -29 + 6x = -77 + 0 -29 + 6x = -77 Add '29' to each side of the equation. -29 + 29 + 6x = -77 + 29 Combine like terms: -29 + 29 = 0 0 + 6x = -77 + 29 6x = -77 + 29 Combine like terms: -77 + 29 = -48 6x = -48 Divide each side by '6'. x = -8 Simplifying x = -8
| 7x-28=17+2x | | 2(6x+6)+8=8x+18 | | 3(2a-2)=2(3a-3) | | 5(3+6x)-4=41 | | 6x^2+33x+42=0 | | x^2-2x+56=0 | | x^2-2x+56=0 | | 6+6(-3-6z)= | | 8(6x-8)-8(2+3x)=-32 | | 5(10+6m)= | | -(6+4x)-8(8x-3)=-50 | | -7+5(2r-6)=-107 | | 5(3x+9)(5x-15)=0 | | (x-4)(x+1)=14 | | e^9x=3 | | 5(1+3b)+7(7-3b)=30 | | -5p+-4(-p+4)= | | 8-11=-13 | | -7x-3=-38 | | y*86=259 | | -5y+3z=12 | | -4(8+7h)+2= | | 9x+9=3y+6 | | 9+9x=6+3y | | 3ab-ab= | | 2x-=3 | | 3y+6=9x+9 | | -9(-9+3j)= | | 6x+y+8x+2y=180 | | -2(a+1)-3(1-7a)=-24 | | 6x+y+8x+2y=0 | | 2x+4x+6x-2(x+3)=34 |